Social factors associated to the multiple risk behaviors among high school students: A case study of Hanoi high school students, Vietnam - Duong Thi Thu Huong (GHMJ (Global Health Management Journal), 2018)
Background: Young people who engaged in different risk behaviors attracted concern nowadays. Noticeably, the concurrent multiple risk behaviors generate adverse effect to health and their future life.Aims: The objectives of this study were to investigate the prevalence of the concurrent multiple risk behaviors and to evaluate the association between social factors and the concurrent multiple risk behaviors among the high school students in Hanoi, Vietnam.Methods: A quantitative survey with a cross sectional design was applied involving a total of 1,333 Hanoi high school students. The survey was conducted in the end of 2016. The multivariate linear regression models were applied to examine the social factors associated with the concurrent multiple risk behaviors of Hanoi high school students. Eighteen different risk behaviors had been selected for constructing a composite variable of the total risk behaviors that students have engaged in.Results: On average, the high school students have been reported involving in 4.88 behaviors of the 18 selected observed risk behaviors. The multivariate linear regression models with demographic factors and different social connections of high school students could explain for about 37.6% of the difference in composite variable of the total risk behaviors. This present study reveals several factors that increase the number of risk behaviors the students may engage, including the connection to the family's members or friends, duration in social media, and the number of friends in the online network. In the contrast, strong family connection has been demonstrated to provide a "safe haven" for protecting the high school students from involving in increasing multiple different risk behaviors.Conclusion: The research findings strongly recommend early prevention strategies should be conducted among the high school students. The identified concurrent risk behaviors should be targeted as prevention actions rather than focusing on controlling individual risk behaviors. In addition, the involvement of their parents and friends are suggested to be the target audience together with students in concurrent risk behaviors controlling and preventing programs among the high school students and young generation. Keywords: Risk behaviors, Social factors, High school students, Adolescents, Vietnam Received: 30 April 2018, Reviewed: 04 June 2018, Received: in revised form 10 October 2018, : Accepted:  21 October 2018 DOI: 10.35898/ghmj-23555